Development of real-time wireless monitoring system for aquaculture industries - Abdullah, Airul Sharizli (2020)
Traditionally, the water quality detection especially for aquaculture industries like shrimp aquaculture has been carried out manually wherein the water samples are collected and taken to the laboratories for analysis. Since these methods fail to deliver real time data, we propose a real time water quality monitoring system based on wireless sensor network which helps in continuous and remote monitoring of the water quality data. The application of wireless sensor network (WSN) for a water quality monitoring is composed of a number of sensor nodes with a networking capability that can be deployed for an ad hoc or continuous monitoring purpose. The parameters involved in the water quality determination such as the pH level, conductivity, dissolve oxygen and temperature is measured in the real time by the sensors that send the data to the base station or control/monitoring room. The use of wireless system for monitoring purpose will not only reduce the overall monitoring system cost in term of facilities setup and labour cost, but will also provide flexibility in term of distance or location. In this project, the fundamental design and implementation of WSN featuring a high power transmission Zigbee based technology together with the IEEE 802.15.4 compatible transceiver is proposed. The water quality data will be display using visual studio platform as graphical user interface (GUI).